Application of redlich-kister modelto measure and predict thermo physical properties of binary liquid mixtures at various temperatures - R., Ramesh; K., Ramesh; Kamal, Yusoh (Penerbit Universiti Malaysia Pahang, 2014)
Study conducts in this research are Viscosities,ŋ, and densities, of 1, 4-dioxane with Benzene at different mole fractions and various temperatures in the atmospheric pressure condition. From experimentations excess volumes, Vᴱ, and deviation sin viscosities,Δŋ, of mixtures at infinite dilutions have been obtained. The measured systems exhibited positive values of Vᶆᴱ and negative values of Δŋ. The binary mixture 1, 4 dioxane + Benzene show positive Vᴱ and negative Δŋ with increasing temperatures. The outcomes clearly indicate that weak interactions present in mixture. It is mainly because of number and position of methyl groups exist in these aromatic hydrocarbons. These measured data tailored to the non-linear models to derive the binary coefficients. Standard deviations areconsidered between the fitted outcomes and the calculated data is helpful deliberate mixing behavior of the binary mixtures. It can conclude that in our cases, the data found with the values correlated by the correspondillg models very well. The molecular interactions existing between the components and comparison of liquid mixtures also discussed.